Особливості застосування електросудомної терапії при наркологічній патології - Чугунов, Вадим Віталійович; Курило, Віталій Олексійович; Данілевська, Наталя Володимирівна; Chugunov, V. V.; Kurilo, V. A.; Danilevska, N. V. (My University, 2016)
Тo examine the possibility of electroconvulsive therapy (ECT) use for the treatment of patients with addiction to psychoactive substances (PAS). The algorithm of ECT, which consists of 3 stages and IX sub-stages is given. The study of the therapeutic viability of ECT in the case of broad spectrum of addictive pathology (F10-F19) in the context of the relief of addictive attraction to PAS and comorbid disorders, including emotional disorders and resistant to pharmacotherapy of pain syndrome is made. ЕСТ is an effective method for additions therapy and comorbide psychopathological states. High therapeutic effect is connected with sanogenetic effect achieved in stopping of poorly curable pathology and achievement of sustained remission even in the cases where other methods are noneffective.
Features of the application of electroconvulsive therapy in the treatment of drug abuse pathology
Keywords: addiction; substance abuse; drug addiction; alcoholism; electroconvulsive therapy